MANAJEMEN PUBLIC RELATIONS DALAM MEMBANGUN CITRA DAN KONTESTASI PERGURUAN TINGGI KEAGAMAAN ISLAM SWASTA (Studi Pada Sekolah Tinggi Agama Islam Syaikhona Moh. Kholil Bangkalan) - Mohammad Hasan (Research Institute and Community Engagement of IAIN MADURA, 2017)
The existence of public relation management has a specific purpose. From some objectives of public relation, there are three points that are prioritized by the Islamic College of Syaichona Moh. Cholil Bangkalan in the management of public relation: first, public relation purposes to improve the quality of education. Second, the purpose of public relation is to improve the image of the college. Third, it aims for communication which is an information management and strategy in college contestation especially in Bangkalan. So the problem in this study are: the first, how are the existence, purpose and function of public relation at Islamic College of Syaichona Moh. Cholil Bangkalan concerning the planning of movement, organizing, and supervision? Second, How the public relation strategy in Islamic College of Syaichona Moh. Cholil Bangkalan to improve the quality of education? Third, how does public relation strategy improve the image of Islamic College of Syaichona Moh. Cholil Bangkalan? Fourth, how is the contestation strategy run using public relation Management at the College of Islamic College of Syaichona Moh. Cholil Bangkalan? This research uses a qualitative-descriptive research methodology, which attempts to describe and interpret objects according to their nature. While the research findings are first, the existence of public relation in Islamic College of Syaichona Moh. Cholil Bangkalan is integrated in each organizations of student organizations, study program, the institutes on the campus and the vice chief that are responsible to the Chief of Islamic College of Syaichona Moh. Cholil Bangkalan. While its objectives and functions are: first, to improve the education quality of Islamic College of Syaichona Moh. Cholil Bangkalan, second, to improve the positive image of Islamic College of Syaichona Moh. Cholil Bangkalan. Third, to increase the power of contestation in the competition colleges in Bangkalan. Fourth, to deliver information and communication to stakeholders of Islamic College of Syaichona Moh. Cholil Bangkalan. First, to identify and analyze the opinions of Islamic College of Syaichona Moh. Cholil Bangkalan. Second, the public relation strategy that is done to increase the quality of education was twofold: first internal education quality improvement of Islamic College of Syaichona Moh. Cholil Bangkalan. Secondly, the improvement of the quality of external education of Islamic College of Syaichona Moh. Cholil Bangkalan. Third, the role of public relation is done in Islamic College of Syaichona Moh. Cholil Bangkalan to improve the image, namely, first, through the development of educational programs, to make more instensive Arabic and yellow bible study curriculum that is integrated in the campus. Second, by working with third-part of campus, such as formal and informal institutions, mosques, prosecutors, courts, Bangkalan district government, news media, the school, and so on. Fourth, the strategy of contestation using Public Relation Management at Islamic College of Syaichona Moh. Cholil Bangkalan are, first, modal social of Islamic College of Syaichona Moh. Cholil Bangkalan, it is a college which is based Islamic boarding school with a big name of Syaichona Moh. Cholil. Second, the strategy of improving the quality of educational services for students. Third, the cooperation strategy with some organizations of the government or non-government. Fourth, doing public communication activities through the press, media, posters, leflets, and means of digital communication.